Analisis Tingkat Pencemar Carbon Monoksida di Udara Akibat Lalulintas dengan Model Polusi Udara Skala Mikro di Jalan MT Haryono Kota Kendari - Akbar, Faharulan; Rosdiana, Rosdiana; Sumarlin, Sumarlin (Universitas Muhammadiyah Kendari, 2022)
Density of motorized vehicle users in Kendari City is one of the factors that affect ambient air quality. This is the reference for conducting this research using a field survey methode for the number of vehicle volumes and ambient air sample testing for air quality in Kendari City with carbon monoxide parameters. The results of this study indicate the daily traffic volume at Jalan MT. Haryono (in front of Pasar Baru). The volume of motorized vehicles of 10,699 units/day (motorcycles), 4,078 units/day (cars) and 272 units/day (heavy equipment). Based on the results of laboratory tests, the CO concentration of the MT. Haryono waypoint (in front of Pasar Baru) Kendari City obtained as follows: in the morning at 4000 μg/m³, in the afternoon at 10350 μg/m³, and in the afternoon at 8000 μg/m³.f The results of measurements carried out the concentration of Carbon Monoxide at points on the MT. Haryono (in front of Pasar Baru). For the morning and evening it is still below the threshold based on the quality standard according to Government Regulation Number 22 of 2021 concerning the Implementation of Environmental Protection and Management. Meanwhile, during the day, the quality standard has passed due to the condition of air temperature, humidity and wind speed which causes the CO concentration to increase.